2015
DOI: 10.1111/ejh.12590
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up study of porcine anti‐human thymocyte immunoglobulin therapy combined with cyclosporine for severe aplastic anemia

Abstract: Immunosuppressive therapy with antithymocyte immunoglobulin (ATG) and cyclosporine A is the first treatment option for severe aplastic anemia (SAA) patients without transplantation. Horse ATG is not marketed in China. Because the price of porcine ATG (pATG) is only about one-third of the price of rabbit ATG (rATG), long-term follow-up studies of pATG's efficacy will help provide valuable insights into the treatment of SAA. Retrospective studies were performed to analyze the clinical information of 102 SAA pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…P-ATG is another preparation, available in China, for clinical use as an immunosuppressive agent, and it is cheaper than R-ATG. One study showed that the drug metabolism curve of P-ATG had an advantage over R-ATG in immunosuppressive therapy; however, the underlying mechanisms were unknown [33]. Results from our hospital (F.K.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…P-ATG is another preparation, available in China, for clinical use as an immunosuppressive agent, and it is cheaper than R-ATG. One study showed that the drug metabolism curve of P-ATG had an advantage over R-ATG in immunosuppressive therapy; however, the underlying mechanisms were unknown [33]. Results from our hospital (F.K.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies [33,36] indicated that P-ATG showed similar efficacy and safety profiles to R-ATG in immunosuppressive therapy of acquired SAA. P-ATG could be a suitable alternative preparation for R-ATG with the advantage of lower medical expense.…”
Section: Discussionmentioning
confidence: 99%
“…Glyco-humanization refers to removal of the αGal epitopes and conversion of animal-type Neu5Gc/Ac forms of sialic acid into human single type Neu5Ac. The procedure has been initially developed to circumvent problems related to the occurrence of high titers of anti-αGal and anti-Neu5Gc antibodies following administration of anti-T lymphocytes rabbit immunoglobulins, which is potentially causing allergies 42 , serum sickness 28 and a possible “xenosialitis”, a systemic inflammation so far only demonstrated in animal models 11,12 . Although our experiments do not directly address the clinical importance of avoiding anti-αGal/Neu5Gc antibody responses, our data show that “natural” anti-pig antibodies found in human serum are essentially directed against Neu5Gc and that reactivity against rabbit IgG is higher than against pig IgG (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although our experiments do not directly address the clinical importance of avoiding anti-αGal/Neu5Gc antibody responses, our data show that “natural” anti-pig antibodies found in human serum are essentially directed against Neu5Gc and that reactivity against rabbit IgG is higher than against pig IgG (Figure 2). These data are of importance in a context where hyperimmune pig immunoglobulins are being used therapeutically to treat aplastic anemia 42,43 and are being developed as an anti-lymphocyte induction treatment in kidney transplantation (NCT 04431219). Glyco-humanized pig immunoglobulins would potentially present, therefore, a safety advantage over rabbit polyclonal antibodies or over immunoglobulins from other species currently in clinical use, such as bovine, horse and goat.…”
Section: Discussionmentioning
confidence: 99%
“…The conditioning regimen, graft-versus-host disease (GvHD) prophylaxis, infection prevention, and surveillance followed those in our previous report ( 14 , 15 ). In particular, pALG was prepared using thymic cells (as antigens) introduced in swine and separating anti-lymphocyte serum from the swine (Wuhan Institute of Biological Products Co., Ltd.) ( 11 , 17 ).…”
Section: Methodsmentioning
confidence: 99%